Implementing Zero Trust Architecture in Multi-Cloud Environments - Manne, Tirumala Ashish Kumar (International Journal of Computing and Engineering, 2023)
Purpose: The purpose of this study is to examine the implementation of Zero Trust Architecture (ZTA) within multi-cloud environments, where traditional perimeter-based security models are increasingly inadequate. The paper aims to identify and address the unique security challenges posed by multi-cloud infrastructures, such as identity and access management (IAM), policy enforcement, network segmentation, and continuous monitoring. Methodology: The research analyzes established industry frameworks, notably NIST Special Publication 800-207, to provide a theoretical foundation for ZTA. It explores practical implementation strategies by evaluating real-world case studies and assessing technologies such as AI-driven threat detection, identity federation, and software-defined perimeters. Comparative analysis of cloud service provider tools and standardization techniques is also conducted to identify best practices for cross-cloud security. Findings: The study finds that implementing ZTA in multi-cloud environments significantly enhances security postures by minimizing attack surfaces and improving regulatory compliance. Effective integration of AI, federated identity solutions, and cloud-native security tools enables continuous verification and least privilege access control. Unique Contribution to Theory, Practice and Policy: The research concludes that while ZTA presents interoperability and policy enforcement challenges, these can be mitigated through standardized frameworks and automation, making ZTA a viable model for modern cloud security.